The influence of singing islamic songs in developing moral values in children at dharma wanita kindergarten, south of aceh - Hijriati, Hijriati; Hasballah, Jamaliah; Rusdiani, Rosi; Rahmi, Putri; Hanifah, Isnaini Amirotun (Amorti: Jurnal Studi Islam Interdisipliner, 2024)
Developing moral values ​​is a process where a child is trained to be sensitive to stimuli, especially regarding the demands of moral values, and learns to get along by behaving politely towards other people in his environment. Developing moral values ​​at Dharma Wanita West Labuhanhaji Kindergarten, South Aceh, is still underdeveloped, because the majority of children are not yet able to behave politely and adapt themselves during the teaching and learning process. The aim of this research is to determine the influence of singing Islamic songs on moral values ​​in early childhood at the Dharma Wanita Kindergarten in West Labuhanhaji, South Aceh. This type of research is experimental with a One Group pretest posttest approach. Data collection was carried out using observation sheets, to see the effect of singing Islamic songs or not. The data analysis techniques used are normality test, homogeneity test and hypothesis test. The research results from data analysis show that the influence of the Islamic song method is to develop children's moral values. In this research it can be concluded that the effect of singing Islamic songs on developing moral values ​​in children is obtained by a calculated t value of 10.528 > t table 12.050. It can be seen in the hypothesis test that a sig value of 0.000 < 0.05 is obtained, meaning that Ha is accepted, Ho is rejected.